The complete classical music guide - Burrows, John, 1939-; Wiffen, Charles; Ainsley, Robert (DK Publishing, 2019)
What makes Mozart's music so great? Why does a minor chord sound sad and a major chord sound happy? What's the difference between opera and operetta? From Bach to Bernstein, this definitive guide offers a complete survey of the history of classical music. Whether you already love classical music or you're just beginning to explore it, The Complete Classical Music Guide invites you to discover the spirituality of Byrd's masses, the awesome power of Handel's Messiah, and the wonders of Wagner's operas, as well as hundreds more composers and their masterpieces. This guide takes you on a journey through more than 1,000 years, charting the evolution of musical instruments, styles, and genres. Biographies of major and lesser-known composers offer rich insights into their music and the historical and cultural contexts that influenced their genius. The book explores the features that defined each musical era - from the ornate brilliance of the Baroque, through the drama of Romantic music, to contemporary genres such as minimalism and electronic music. Timelines, quotes, and colour photographs give a voice to this music and the exceptionally gifted individuals who created it. Covering both music history and the fundamental building blocks of music theory, The Complete Classical Music Guide explains not just the who, what, and where of classical music, but the how and why.